Heterozygosity at the canarc-1 locus can confer susceptibility for narcolepsy: induction of cataplexy in heterozygous asymptomatic dogs after administration of a combination of drugs acting on monoaminergic and cholinergic systems - Mignot, E (J Neurosci, 1993)
Narcolepsy is a genetically determined disorder of sleep characterized by excessive daytime sleepiness and abnormal manifestations of REM sleep that affects both humans and animals. Although its exact pathophysiologic mechanisms remain undetermined, recent experiments have demonstrated that in both humans and canines, susceptibility genes are linked with immune-related genes. A striking difference, however, is that the genes thought to be involved in the human pathology are autosomal dominant, whereas canine narcolepsy in Dobermans is transmitted as a single autosomal recessive gene with full penetrance (canarc-1). In this study, we have examined the development of narcoleptic symptoms in homozygous narcoleptic, heterozygous, and control Dobermans. Animals were behaviorally observed until 5 months of age and then treated at weekly intervals with cataplexy-inducing compounds that act on cholinergic or monoaminergic systems (alone and in combination). Our data indicate that cataplexy can be induced in 6- month-old asymptomatic heterozygous animals, but not in control canines, with a combination of drugs that act on the monoaminergic and cholinergic systems. This demonstrates that disease susceptibility may be carried by heterozygosity at the canarc-1 locus. Our data further suggest that cataplexy, a model of REM sleep atonia, is centrally regulated by a balance of activity between cholinergic and monoaminergic neurons.